Reference data on atomic physics and atomic processes - Smirnov, B. M. (Springer, 2017)
This book is a data book for atomic and plasma physicists. Numerical data are given for atoms, atomic processes and atomic systems along with basic concepts and simple models for atomic physics of this area. Information of the same type for elements, for example atom and ion ionization potentials, is represented in the form of periodical tables. Atomic spectra and potential curves of diatomic molecules are given together with formulas and unit conversional factors for quantities of atomic physics and physics of ionized gases.